The Relationship Between Parenting Style and Emotional Maturity of Adolescents from Single-Parent Families - Jane, Febe; Ambarwati, Krismi Diah (Analitika: Jurnal Magister Psikologi UMA, 2025)
One form of family disharmony is the presence of a single parent, which often results from divorce. This condition can impact adolescent development, particularly emotional maturity. This study aims to examine the relationship between parenting style and emotional maturity among adolescents from single-parent families. A quantitative approach with a correlational design was employed. The participants consisted of 52 adolescents aged 12–18 years from single-parent families due to divorce. The instruments used were the Parenting Styles and Dimensions Questionnaire (PSDQ) to measure parenting style and the Emotional Maturity Scale (EMS) to assess emotional maturity. Data were analyzed using Pearson’s correlation test. The results revealed a significant positive relationship between general parenting style and adolescents’ emotional maturity (r = 0.420; p = 0.001). However, no significant correlation was found between authoritarian or permissive parenting styles and emotional maturity. These findings suggest that certain parenting styles play an important role in shaping the emotional development of adolescents from single-parent families.